Cognitive Dissonance and Public Compliance, and Their Impact on Business Performance in Hotel Industry - Xi, Wen; Baymuminova, Nigora; Zhang, Yi-Wei; Xu, Shi-Nyu (Sustainability, 2022)
In this study, we investigate whether cognitive dissonance and compliance with collective rationality affect hotel CEO management activities. The study surveyed a wide range of hotel employees, from new recruits to CEOs, within 5-star hotels in Seoul to analyze perceptions of organizational members. A canonical correlation analysis was used to empirically investigate the correlations and differences among constitutional concepts. The study also used regression analysis to analyze the influential relationship between variables. The study found that despite the differences in individual beliefs, compliance to collective beliefs increased when individuals complied and received compensation despite their individual differences. The performance perceptions of financial and non-financial management improved at that time. Some research conducted on the Cognitive Dissonance also demonstrates that individuals with cognitive dissonance modify their behavior and cognition to reduce dissonance. It is true that an individual’s opinion differs from that of the group, but adding a cognitive factor that an individual is compensated by participating in and respecting the group’s beliefs leads to public compliance with those beliefs. Due to the strong public cognition and beliefs within the organization, the individual attempts to keep his or her cognitive and belief systems consistent, but complies with them regardless of his or her cognitive and belief systems. Furthermore, it suggests that managers can improve their performance by compensating people for conforming to group rules, since management performance is the end goal of management, and public compliance affects it significantly.